Breve Memoría Fotográfica del Dr. Sergio Moreno Limón - Alvarado Vázquez, Marco Antonio; Salcedo Martínez, Sergio Manuel (Universidad Autónoma de Nuevo León, 2025)
Se presenta una breve memoria fotográfica del Dr. Sergio Moreno Limón.